English for tourism and restaurants Book 2 - Levin, Frank; Tinsley, Peg; Majewski, Judy (Tp. Hồ Chí Minh Tổng hợp Tp. Hồ Chí Minh, 2016)
Contents: Pronunciation and Intonation; Greetings and Self-Introduction; Cardinal Numbers; Cardinal Numbers and Ordinal Numbers; Offering Apologies; Offering Polite Refusals and Saying Thanks; Expressions of Time; Expressions of Dates
Keywords: Ngôn ngữ Anh